2019
DOI: 10.1016/j.jsxm.2019.11.267
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-institutional Assessment of Multimodal Analgesia in Penile Implant Recipients Demonstrates Dramatic Reduction in Pain Scores and Narcotic Usage

Abstract: Introduction Despite the pain associated with inflatable penile prosthesis (IPP) implantation, there has been a lack of standardized, nonopioid pain control regimens described to date. Aim To assess the effectiveness of a multimodal analgesic regimen in patients undergoing implantation of an IPP compared with patients treated with an opioid-only regimen. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Studies in other medical disciplines have also examined postoperative opioid prescription patterns with multimodal treatment, providing support for their use. The use of multimodal analgesia was associated with reduced frequency of opioid prescriptions at discharge among 528 patients undergoing thyroid and parathyroid surgery [15]; and a reduction in opioid use and improvement in pain control among patients undergoing penile implant surgery [16]. Implementation of a multimodal analgesic regimen after common arthroscopic procedures, including meniscectomy, rotator cuff repair, and ACL reconstruction, showed a significant decrease in the amount of opioid pain medication prescribed in the postoperative period with the multimodal regimen [17].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other medical disciplines have also examined postoperative opioid prescription patterns with multimodal treatment, providing support for their use. The use of multimodal analgesia was associated with reduced frequency of opioid prescriptions at discharge among 528 patients undergoing thyroid and parathyroid surgery [15]; and a reduction in opioid use and improvement in pain control among patients undergoing penile implant surgery [16]. Implementation of a multimodal analgesic regimen after common arthroscopic procedures, including meniscectomy, rotator cuff repair, and ACL reconstruction, showed a significant decrease in the amount of opioid pain medication prescribed in the postoperative period with the multimodal regimen [17].…”
Section: Discussionmentioning
confidence: 99%
“…The same protocol was validated in a multi-institutional cohort of men undergoing IPP implantation. In this investigation, men who received MMA again had lower VAS scores in PACU and through POD #1, required less opioids while hospitalized, and had less refills for opioid medication (32). To our knowledge, these investigations represent some of the only rigorous characterizations of pain response following penile implantation that help traverse the entire recovery period.…”
Section: Multimodal Analgesiamentioning
confidence: 78%
“…The devastating effects of the opioid epidemic have prompted various interventions, including prescribing guidelines and enhanced recovery after surgery (ERAS) pathways (10)(11)(12). Recently, Lucas et al evaluated the combination of acetaminophen, meloxicam or celecoxib, gabapentin, and penile/pudendal nerve blocks with local anesthetic (using a mixture of lidocaine and bupivacaine) compared to an opioid-based pain management regimen following inflatable penile prosthesis procedures (29). Using this protocol, the authors found a significant decrease in postoperative pain coupled with lower oral opioid consumption when compared with a historical opioidbased regimen.…”
Section: Discussionmentioning
confidence: 99%